Stefka Georgieva Eriksen (ed.): Intellectual Culture in Medieval Scandinavia, c. 1100-1350. - Münster-Swendsen, Mia (Collegium Medievale, 2019)
The book contains thirteen essays mainly by Nordic scholars covering an eclectic array of topics, such as grammatical treatises, visual arts, liturgy, vernacular as well as Latin texts, the sagas, poetry, and manuscript fragments. The individual, often highly specialized contributions are divided into three sub-sections, following the two introductory essays "Intellectual Culture and Medieval Scandinavia" by Stefka Georgieva Eriksen (the editor) and Gunnar Harðason's survey of Old Norse intellectual culture. The first sub-section contains essays dealing with various processes of identity formation, introduced by a survey of aspects of the thirteenth-century intellectual milieu in Paris by Ian P. Wei. Like the former, the second section, "Thinking in figures" is headed by a broad essay by a leading scholar in the field, Rita Copeland. The third and final section deals with the juxtaposition of earthly existence and heavenly salvation.